Aspek Hukum dalam Kegagalan Struktur Mekanis Analisis Teknik dan Tanggung Jawab Hukum - Imam Saputra; Sahrul Saputra; Rahmawaty Rahmawaty; Sultan Rexy Adji (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Structural failure in construction projects is a critical issue that not only endangers public safety but also triggers legal consequences for parties involved. This study explores mechanical structural failure from technical, legal, and professional responsibility perspectives. Technically, structural failures are often caused by inadequate planning, poor-quality materials, and improper construction practices. Legally, the Indonesian Construction Services Law (Law No. 2 of 2017) and the Indonesian Criminal Code (KUHP) provide a foundation for holding parties accountable, both civilly and criminally, especially when failures result in significant losses or casualties. The research also discusses the roles and responsibilities of construction consultants and contractors. Consultants are responsible for accurate design and oversight, while contractors must ensure implementation aligns with technical specifications and safety standards. Any negligence or deviation from duties by either party can lead to legal liability. This paper emphasizes the importance of integrating technical diligence with legal compliance to ensure the success and safety of construction projects.